ChemInform Abstract: Synthesis of Chiral 4, 5‐Dihydrothiazol‐2‐amines and 4, 5‐Dihydrooxazol‐2‐amines Through an Unexpected Ring Opening Reaction of Azetidines. Issue 28 (June 2016) - Zhou, Xin; Xu, Xingyu; Li, Yi; Zhang, Zhanbin; Zheng, Zhi‐bing
Abstract: Chiral azetidines (I) react with isocyanates or isothiocyanates to form the corresponding urea intermediates, which undergo a completely regio‐ and stereoselective ring opening reaction to furnish oxazoles (IV) or thiazoles (VI).